2008
DOI: 10.1097/aud.0b013e3181645366
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of the Vibrant Soundbridge Device in Patients Implanted For 5 to 8 Years

Abstract: This study demonstrates that the performance of the VSB does not deteriorate for more than 5 yr, without adverse effect. These results confirm the safety and the effectiveness of the VSB with a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 12 publications
(31 reference statements)
8
57
0
4
Order By: Relevance
“…In the study presented here, we found no indication of an accelerated age-related hearing loss associated with the implantation of the VSB. This result is in accordance with the multicentre study by Mosnier et al [2008] covering a mean observation time of 6 years after implantation. Earlier findings, indicating an accelerated progression in AC hearing loss in the implanted ear after 42 months (8 vs. 2.6 dB) without differentiation between the surgery-related effects on AC and BC thresholds, could not be verified [Schmuziger et al, 2006].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study presented here, we found no indication of an accelerated age-related hearing loss associated with the implantation of the VSB. This result is in accordance with the multicentre study by Mosnier et al [2008] covering a mean observation time of 6 years after implantation. Earlier findings, indicating an accelerated progression in AC hearing loss in the implanted ear after 42 months (8 vs. 2.6 dB) without differentiation between the surgery-related effects on AC and BC thresholds, could not be verified [Schmuziger et al, 2006].…”
Section: Discussionsupporting
confidence: 92%
“…Since proven to be an alternative solution in individuals with moderate-to-severe SNHL, the so-called incus vibroplasty has become a routine clinical procedure. Nevertheless, there are only few reports on the long-term safety and efficacy of the implants as only two studies, one in the USA [Luetje et al, 2010] and another with a multicentre design in France [Mosnier et al, 2008], have reported results on a wearing time longer than 5 years. Therefore, it is important to provide more evidence of the long-term safety and efficacy of the VSB.…”
Section: Introductionmentioning
confidence: 99%
“…The results for hearing restoration in sensorineural hearing loss and recently in mixed and conductive hearing loss are reliable and stable in the long term [Fisch et al, 2001;Lenarz et al, 2001;Todt et al, 2002;Mosnier et al, 2008;Streitberger et al, 2009;Böheim et al, 2012;Huber et al, 2012]. However, the surgical approach and the variability in audiological outcome as well as the benefit when compared to conventional hearing aids are controversial, especially with regard to the classical application at the long incus process Snik et al, 2001;Junker et al, 2002;Schmuziger et al, 2006;Truy et al, 2006;Bruschini et al, 2009].…”
Section: Surgical Issuesmentioning
confidence: 97%
“…Their short-and long-term efficacy and safety is now established [Sterkers et al, 2003;Vincent et al, 2004;Mosnier et al, 2008]. Based on these data, and the ability of these devices to deliver amplified sound energy in the middle ear, the idea of placing the transducer close to the cochlea in case of abnormal middle ear emerged.…”
Section: Introductionmentioning
confidence: 99%